Los límites de las burguesías nacionales - Barrios Graziani, Leticia (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
In the present essay analyzes the roles of the national bourgeoisies in the Latin American societies and individual the behavior of the Venezuelan bourgeoisie and the foreign capital in last the four decades. In this analysis the weak contribution carried out by these sectors in the national development stands out; the evolution and the transformations experienced in each one of the implanted economic models in the country, as well as the main alliances and contradictions established with the rest of the sectors of the society.